Sensitive Carbon Fiber Microelectrode for the Quantification of Diuron in Quality Control of a Commercialized Formulation - Serge Mbokou Foukmeniok; Roland Fabrice Yibor Bako; Ousmane Ilboudo; Yssouf Karanga; Evangéline Njanja; Maxime Pontie; Issa Tapsoba; Ignas Tonle Kenfack; Rousseau Djouaka (International Journal of Analytical Chemistry)
Nickel(II) tetrasulfonated phthalocyanine (p-NiTSPc)-modified carbon fiber microelectrode (CFME) was used for the first time to investigate the electrochemical quantification of diuron in an agrochemical formulation. The surface morphology and elementary analysis of unmodified carbon fiber microelectrode (CFME) and p-NiTSPc-CFME were performed using atomic force microscopy (AFM) and energy dispersive X-ray spectroscopy (EDX), respectively. Cyclic voltammetry (CV) was used to investigate the electrochemical behaviour of diuron, while square wave voltammetry (SWV) was used for quantitative analysis of diuron. Upon variation of some key analytical parameters, a calibration curve was plotted in the concentration range from 21.450 to 150.150 μM, leading to a detection limit (DL) of 8.030 μM mg/L (3.3σ/m) and a limit of quantification (LQ) of 20.647 μM mg/L. The fabricated p-NiTSPc-CFME was successfully applied for quality control in a commercialized formulation of diuron. The standard additional method was used, and the recovery rate of diuron was found to be 98.4%.